Risk assessment of cancer of the female reproductive system - Glushchenko, N.M.; Nesina, I.P.; Lurchenko, N.P.; Proskurnya, L.A.; Buchynska, L.G. (Experimental Oncology, 2014)
Aim: To create an information resource concerning multifactorial oncological diseases of the female reproductive system. Materials and Methods: A comprehensive search of the literature in the PubMed and Ukrainian scientific sources published from 1995 to 2014 and the results of researches performed in R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology, National Academy of Sciences of Ukraine. Development environment of information resource “Multifactorial oncological disease” was Borland Delphi. Results: The information content of web page concerning cancers of the female reproductive system was posted in the information resource “Multifactorial oncological disease”. The assessment algorithm of genetic contribution to cancers of the female reproductive system and recurrent risk of cancer development in families have been described. These algorithms can be used in assessment of contribution of genetic and environmental factors in the development of malignant tumors. Key Words: cancers of the female reproductive system, information resource, genetic contribution, recurrent risk.